An overview of the current knowledge of jumping plant-lice of Slovenia (Hemiptera: Psylloidea) - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2006)
A list of the jumping plant-lice (Psylloidea) species recorded in Slovenia is given: 100 species have been found of which 44 are new to the Slovenian fauna.The records of Trioza kiefferi Giard were based on misidentification, and the species is considered as absent from Slovenia.
Keywords: bolšice; entomologija; insekti; Slovenia; Slovenija